A Comparative Study of Contract Formation and Breach of Contract and Liability in China and OHADA Space Contract Laws - Traoré, Moussa Sékou; Xiao, Yongping (Journal of Politics and Law, 2011)
Chinese politicians and businessmen and their African counterparts are improving economic and commercial relations between them. This manifest interest of partnership needs a legal framework which guarantees equal and fair advantages to both parties. To reach this global aim, China and Africa must develop their collaboration in the domain of law. In the 80s China has adopted laws to reflect the country's economic and social demands such as Economic Contract Law (1981), Foreign Economic Contract Law (1985), General Principles of Civil Law (1987). Now, to better facilitate economic growth the National People's Congress (NPC) has unified China's various national specialized contract laws to obtain the “Uniform” Contract Law 1999. OHADA is a system that aims the harmonization of business law in Africa. This study aims to compare the two systems contract formation, breach of contract and liability for breach in order to have a legal frame more appropriate for business between China and this part of African Continent.

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa